2022
DOI: 10.3389/fgene.2022.833694
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Wide Analysis of RNA N6-Methyladenosine Modification in Adriamycin-Resistant Acute Myeloid Leukemia Cells

Abstract: Acute myeloid leukemia (AML) is one of the most aggressive hematopoietic malignancies. Patients still suffer from refractory/relapsed disease after anthracycline-based therapy, which leads to a poor prognosis. N6-Methyladenosine (m6A) is the most abundant post-transcriptional modification in eukaryotes, the imbalance of which is reported to be associated with various pathological processes, including drug resistance. However, the relationship between m6A modification and drug resistance has not been well defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…However, a majority of relapsed or drug-resistant AML patients have mutations in the deoxycytidine kinase gene, resulting in increased resistance to pharmacotherapy and eventual treatment failure [28]. Recently, studies have shown that mRNA methylation under the regulation of methyltransferase 3 (METTL3) may be involved in the regulation of drug resistance in AML [29,30]. Here, we report the signi cant alteration in global gene expression pro les in mononuclear cells from bone marrow blood in relapsed or drug-resistant AML patients compared with AML remission and Healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, a majority of relapsed or drug-resistant AML patients have mutations in the deoxycytidine kinase gene, resulting in increased resistance to pharmacotherapy and eventual treatment failure [28]. Recently, studies have shown that mRNA methylation under the regulation of methyltransferase 3 (METTL3) may be involved in the regulation of drug resistance in AML [29,30]. Here, we report the signi cant alteration in global gene expression pro les in mononuclear cells from bone marrow blood in relapsed or drug-resistant AML patients compared with AML remission and Healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…While METTL3 and FTO have opposing roles in the regulation of m 6 A modification, it's noteworthy that due to differences in the signaling pathways involved, genetic knockdown of either of these genes enhances the sensitivity of BC cells to doxorubicin. METTL3 has also been found to be involved in doxorubicin resistance of AML cells, and inhibition of METTL3 increased the sensitivity of drug-resistant cells and inhibited the proliferation of doxorubicin resistant HL60/ADR cells [ 157 ]. Moreover, WTAP has also been implicated in the resistance of AML cells to doxorubicin [ 158 ].…”
Section: Potential Of M 6 a In Cancer Therapymentioning
confidence: 99%